The effects of swimming fatigue on shoulder strength, range of motion, joint control, and performance in swimmers - Matthews, M. J.; Green, D.; Matthews, H.; Swanwick, E. (Physical Therapy in Sport, 2017)
• Reductions observed in swim stroke length with fatigue. • Reductions observed in external rotation range of motion of both arms with fatigue. • Reduction observed in joint position sense of dominant arm. • No changes observed in isometric strength with fatigue.